Vinylphenanthroline covalent organic framework material and preparation method and application thereof

CN117551249BActive Publication Date: 2026-10-09HEBEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311500784.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2026-10-09
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

[0006]为此,本发明提供一种乙烯基菲罗啉共价有机框架材料及其制备方法和应用,用以解决当前构建乙烯基共价有机框架所需活性甲基单体的紧缺以及在光催化应用中催化活性低的技术问题

Benefits of technology

[0023] (1) The covalent organic framework material of the present invention is simple and easy to prepare, and can be obtained by solvothermal method; at the same time, as a photocatalytic material, the catalytic reaction is carried out at room temperature, only visible light irradiation is required, the catalytic conditions are simple, and the catalytic process is energy-saving and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117551249B_ABST
    Figure CN117551249B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photocatalysis, and particularly relates to a vinylphenanthroline covalent organic framework material and a preparation method and application thereof. After mixing reactants 2,9-dimethyl-1,10-phenanthroline and aldehyde monomers, a solvent and a catalyst are added, and the vinylphenanthroline covalent organic framework material is prepared through a solvothermal reaction. The vinylphenanthroline covalent organic framework material obtained through the preparation method is applied to photocatalytic decomposition of water to hydrogen and oxygen as a catalyst. Meanwhile, a sacrificial reagent and a cocatalyst precursor are added to water, and a reaction is carried out under visible light irradiation, and the vinylphenanthroline covalent organic framework material has high hydrogen evolution and oxygen evolution activity. The application has the beneficial effects that the preparation method is simple and easy to implement, the prepared material has good thermal stability, and efficient visible light catalytic hydrogen evolution and oxygen evolution can be realized. Meanwhile, the catalyst can be recycled, and has good photocatalytic reaction stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, and particularly relates to a vinylphenanthroline covalent organic framework material, its preparation method, and its application. Background Technology

[0002] In the 21st century, the energy crisis and environmental pollution are two major serious problems facing humanity. Photocatalytic water splitting to produce "green hydrogen" is of great significance in solving these problems. Semiconductor materials are commonly used as catalysts in the field of photocatalysis. Among them, COFs (Chemical Oxide-Coated Foliar Materials) are novel crystalline organic porous materials formed by covalently linked structural building blocks. They possess characteristics such as large specific surface area, good chemical stability, easily tunable structure, and wide light absorption range, attracting widespread attention in the field of photocatalytic solar energy conversion. Since the first COF material was reported in 2005, a large number of boron ester or imine-bonded COFs have been synthesized. However, due to the good reversibility of these chemical bonds, COFs suffer from significant defects in stability and charge transfer. Vinyl-linked COFs can fundamentally overcome these shortcomings, thereby expanding the application prospects of COF materials. However, constructing vinyl COFs requires strongly electron-withdrawing substituents to stabilize highly reactive intermediates. To date, the types of monomers suitable for constructing vinyl-linked COFs are very limited. Finding new functional monomers, expanding the variety of vinyl-functionalized COFs, and exploring their applications are urgent and challenging tasks. phenanthroline is an inexpensive, planar, rigid, hydrophobic, electron-conjugated, and electron-withdrawing heterocyclic aromatic ligand with wide applications in coordination chemistry and homogeneous organic catalysis. It can serve as an active methyl monomer and aldehyde monomer in the construction of vinyl covalent organic frameworks.

[0003] The main factors affecting the photocatalytic activity of semiconductor materials include: catalyst light absorption, charge separation, and surface catalytic reaction efficiency. To date, researchers typically employ strategies such as band structure modulation, doping, and compositional adjustment to construct highly efficient photocatalytic systems.

[0004] Combining COFs materials with a wide absorption range with cocatalysts to form a tight interface that facilitates charge transport can improve the charge separation and catalytic conversion efficiency of COFs, potentially leading to a highly efficient COFs-based photocatalytic water splitting system for hydrogen production. For example, Chinese patent CN 114570429A discloses a single-atom-supported covalent organic framework material, its preparation, and its application in photocatalytic water splitting for hydrogen production. Utilizing the characteristic of sulfur atoms anchoring metal atoms, sulfur-containing groups are introduced into the pores of the covalent organic framework. These sulfur-containing groups, along with solvent molecules, further anchor the single atom, which not only improves the stability of the single atom but also facilitates charge transfer between the single atom and the covalent organic framework, thereby increasing the system's photocatalytic water splitting efficiency for hydrogen production. Furthermore, the water oxidation reaction involves a complex four-electron transfer process and has a high reaction barrier, meaning that most COFs can only drive hydrogen production reactions and cannot simultaneously achieve bifunctional hydrogen and oxygen production reactions. The nitrogen atoms in phenanthroline-based COFs can interact strongly with metal cocatalysts, allowing photogenerated charges to be rapidly transferred from the catalyst to the cocatalyst and then quickly participate in subsequent catalytic reactions. This promotes charge separation and catalytic conversion processes to a certain extent, making it beneficial for photocatalytic reactions.

[0005] Therefore, finding new methyl functional monomers, expanding the variety of vinyl-functionalized COFs, and exploring efficient, bifunctional photocatalysts for hydrogen and oxygen production are among the most important and challenging tasks at present. Summary of the Invention

[0006] Therefore, this invention provides a vinylphenanthroline covalent organic framework material, its preparation method, and its application, in order to solve the technical problems of the current shortage of active methyl monomers required for constructing vinyl covalent organic frameworks and their low catalytic activity in photocatalytic applications.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A method for preparing a vinylphenanthroline covalent organic framework material includes the following steps: mixing reactant 2,9-dimethyl-1,10-phenanthroline (DP) and an aldehyde monomer, adding a solvent and a catalyst, and preparing the vinylphenanthroline covalent organic framework material by a solvothermal reaction.

[0009] Preferably, the molar ratio of the aldehyde monomer to 2,9-dimethyl-1,10-phenanthroline is 1:1.5.

[0010] Preferably, the aldehyde monomer is 1,3,5-tris(4-formylphenyl)triazine (TFPT) or 1,3,5-tris(p-formylphenyl)benzene (TFPB).

[0011] Preferably, the solvent is a mixed solution of N,N-dimethylformamide (DMF) and o-dichlorobenzene (o-DCB), the catalyst is trifluoromethanesulfonic acid (TfOH), and the volume ratio of N,N-dimethylformamide, o-dichlorobenzene and trifluoromethanesulfonic acid is 7:3:1.5.

[0012] Preferably, the mass ratio of the reactants to the volume of the solvent and catalyst mixture is 12-13 mg / mL.

[0013] Preferably, the reaction temperature is 180℃ and the reaction time is 72-80h; after the reaction, the product is washed sequentially with anhydrous methanol, tetrahydrofuran and dichloromethane, and then vacuum dried at a temperature of 60-80℃ for 6-10h.

[0014] Preferably, the washing process of the product is as follows: washing with anhydrous methanol 3-5 times, washing with dichloromethane 3-5 times, and washing with tetrahydrofuran 3-5 times;

[0015] This invention also provides a vinylphenanthroline covalent organic framework material obtained by the above preparation method. The structural formula of its structural unit is shown below:

[0016]

[0017] The present invention also provides an application of the above-mentioned vinylphenanthroline covalent organic framework material in photocatalytic water splitting for hydrogen and oxygen evolution.

[0018] Preferably, a vinylphenanthroline covalent organic framework material, a sacrificial reagent, and a cocatalyst precursor are added to water, and a water-decomposing reaction is carried out under visible light irradiation, wherein the vinylphenanthroline covalent organic framework material serves as a catalyst for water decomposition.

[0019] Preferably, the wavelength of the visible light is λ≥420nm.

[0020] Preferably, in the hydrogen production reaction, the amount of vinylphenanthroline covalent organic framework material added to water is 20 mg / L; the sacrificial reagent is ascorbic acid, the concentration of ascorbic acid in water is 0.1 mol / L, the cocatalyst is platinum, and the mass ratio of metallic platinum to catalyst in water is 0.5-5 wt%; the solution after the reaction is completed is filtered and washed to obtain vinylphenanthroline covalent organic framework material again.

[0021] Preferably, in the oxygen generation reaction, the amount of vinylphenanthroline covalent organic framework material added to the water is 20 mg / L; the sacrificial reagent is ascorbic acid, the concentration of ascorbic acid in the water is 0.1 mol / L, the co-catalyst is cobalt, and the mass ratio of metallic cobalt to catalyst in the water is 0.5-5 wt%; the solution after the reaction is completed is filtered and washed to obtain vinylphenanthroline covalent organic framework material again.

[0022] The beneficial effects of this invention are as follows:

[0023] (1) The covalent organic framework material of the present invention is simple and easy to prepare, and can be obtained by solvothermal method; at the same time, as a photocatalytic material, the catalytic reaction is carried out at room temperature, only visible light irradiation is required, the catalytic conditions are simple, and the catalytic process is energy-saving and environmentally friendly.

[0024] (2) The covalent organic framework material prepared by this invention has excellent thermal stability and can maintain structural stability below 400℃.

[0025] (3) The covalent organic framework materials prepared in this invention exhibit excellent photocatalytic activity in photocatalytic hydrogen production, which is attributed to the interaction between the covalent organic framework materials and the metal cocatalyst. Among them, PVCOF-1 and PVCOF-2 are rich in nitrogen atoms, which can generate strong interactions with the metal cocatalyst, enabling the effective separation and rapid transfer of photogenerated charges to the active sites for oxidation or reduction reactions; in addition, due to the conjugated characteristics of vinyl-linked COFs materials, this characteristic improves their charge separation efficiency, which may further enhance the catalytic performance of the materials.

[0026] (4) The covalent organic framework material prepared by the present invention can be recycled. After four long-term photocatalytic reactions, the catalytic activity did not change significantly, and the original morphology of the material was well maintained, showing good stability of photocatalytic reaction. Attached Figure Description

[0027] Figure 1 Here is the synthesis equation for COFs materials;

[0028] Figure 2 Here is the powder XRD pattern of PVCOF-1 material;

[0029] Figure 3 SEM image of PVCOF-1 material;

[0030] Figure 4 Here is the powder XRD pattern of PVCOF-2 material;

[0031] Figure 5 SEM image of PVCOF-2 material;

[0032] Figure 6 FT-IR images of PVCOFs materials and reactant monomers;

[0033] Figure 7 Thermogravimetric analysis diagram of PVCOFs material;

[0034] Figure 8 The UV-Vis diffuse reflectance spectrum of PVCOFs material;

[0035] Figure 9 The visible light photocatalytic hydrogen evolution performance of PVCOF-1 material under different platinum loading conditions is shown in the figure.

[0036] Figure 10 The visible light photocatalytic oxygen evolution performance of PVCOF-1 material under different cobalt loading conditions is shown in the figure.

[0037] Figure 11 Figure 1 shows the visible light photocatalytic water splitting hydrogen production performance of PVCOFs material with a platinum loading of 3 wt%;

[0038] Figure 12 Figure 1 shows the visible light photocatalytic water splitting oxygen production performance of PVCOFs material with a 3wt% cobalt loading.

[0039] Figure 13 The graph shows the 24-hour cycle performance of the visible light catalytic water splitting and hydrogen evolution reaction of PVCOF-1 material.

[0040] Figure 14 Impedance plot of COFs material;

[0041] Figure 15 This is a photocurrent plot of COFs materials. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0043] In this invention, the reactants 2,9-dimethyl-1,10-phenanthroline (DP), 1,3,5-tris(4-formylphenyl)triazine (TFPT) and 1,3,5-tris(p-formylphenyl)benzene (TFPB) are all commercially available products.

[0044] Example 1

[0045] In this embodiment, PVCOF-1, a vinylphenanthroline covalent organic framework material, was prepared using 2,9-dimethyl-1,10-phenanthroline (DP) and 2,4,6-tris(4-aldehydephenyl)-1,3,5-triazine (TFPT). The reaction formula is as follows: Figure 1 As shown, the preparation method includes the following steps:

[0046] (1) Weigh 62.48 mg (0.3 mmol) of 2,9-dimethyl-1,10-phenanthroline and 78.68 mg (0.2 mmol) of 1,3,5-tris(4-formylphenyl)triazine and put them into a heat-resistant tube. Then add a mixed solution consisting of N,N-dimethylformamide (7 mL), o-dichlorobenzene (3 mL) and trifluoromethanesulfonic acid (1.5 mL) and sonicate at room temperature until well mixed.

[0047] (2) The heat-resistant tube was heated in an oil bath at 180°C for 80 h. The reaction progressed from a clear solution to the formation of a yellow-green solid. After the reaction was completed, the product was washed three times with anhydrous methanol, three times with tetrahydrofuran, and three times with dichloromethane. Then, it was vacuum dried at 60°C for 10 h to obtain 129 mg of covalent organic framework material PVCOF-1 with a yield of 91%.

[0048] The prepared PVCOF-1 was subjected to powder XRD testing (instrument model: D8 Discover, Bruker). The test results are as follows: Figure 2 As shown, a distinct diffraction peak exists at 2θ = 7.4°, confirming that the covalent organic framework material is crystalline.

[0049] The prepared PVCOF-1 was analyzed by scanning electron microscopy (instrument model: FEI Nova Nano SEM450 instrument), and the SEM images are shown below. Figure 3 As shown, this indicates that the material is a solid powder.

[0050] The prepared PVCOF-1 and raw material monomers DP and TFPT were subjected to Fourier transform infrared spectroscopy (instrument model: TENSOR 27 spectrometer). The obtained Fourier transform infrared spectra are shown below. Figure 6 As shown. From Figure 6 It can be seen that the C=O stretching vibration peak of TFPT is (1694 cm⁻¹). -1 Significant attenuation was observed at 966 and 1610 cm⁻¹. -1 The presence of a strong stretching vibration peak of the ethylene bond (C=C) confirms the high degree of condensation polymerization of PVCOF-1.

[0051] The prepared PVCOF-1 was subjected to thermogravimetric analysis (instrument model: TA SDT-TG Q600 thermogravimetric analyzer), and the obtained thermogravimetric analysis chromatogram is shown below. Figure 7 As shown, thermogravimetric analysis revealed that the material structure remained relatively stable at 400℃ under nitrogen protection, indicating that the catalyst exhibits good stability under both room temperature and higher temperature conditions.

[0052] In addition, UV-Vis diffuse reflectance spectroscopy analysis was performed on PVCOF-1 (instrument model: Shimadzu UV-3600i Plus spectrophotometer), and the results are as follows: Figure 8 As shown, the light absorption range of this material is approximately 615 nm.

[0053] Example 2

[0054] In this embodiment, PVCOF-2, a vinylphenanthroline covalent organic framework material, was prepared using 2,9-dimethyl-1,10-phenanthroline (DP) and 1,3,5-tris(p-formylphenyl)benzene (TFPB). The reaction formula is as follows: Figure 1 As shown, the preparation method includes the following steps:

[0055] (1) Weigh 62.48 mg (0.3 mmol) of 2,9-dimethyl-1,10-phenanthroline and 78.08 mg (0.2 mmol) of 1,3,5-tris(p-formylphenyl)benzene and put them into a heat-resistant tube. Then add a mixed solution consisting of N,N-dimethylformamide (7 mL), o-dichlorobenzene (3 mL) and trifluoromethanesulfonic acid (1.5 mL) and sonicate at room temperature until well mixed.

[0056] (2) The heat-resistant tube was heated in an oil bath at 180°C for 80 h; the reaction proceeded from a clear solution to the formation of a red solid. After the reaction was completed, the product was washed three times with anhydrous methanol, three times with tetrahydrofuran, and three times with dichloromethane. Then, it was vacuum dried at 60°C for 10 h to obtain 126 mg of covalent organic framework material PVCOF-2 with a yield of 90%.

[0057] The prepared PVCOF-2 was subjected to powder XRD testing (instrument model: D8 Discover, Bruker). The test results are as follows: Figure 4 As shown, a distinct diffraction peak exists at 2θ = 7.6°, confirming that the covalent organic framework material is crystalline.

[0058] The prepared PVCOF-2 was analyzed by scanning electron microscopy (instrument model: FEI Nova Nano SEM450 instrument), and the SEM images obtained are shown below. Figure 5As shown, this indicates that the material is a solid powder.

[0059] The prepared PVCOF-2 and raw material monomers DP and TFPB were subjected to Fourier transform infrared spectroscopy (instrument model: TENSOR 27 spectrometer). The obtained Fourier transform infrared spectra are shown below. Figure 6 As shown. From Figure 6 It can be seen that the C=O stretching vibration peak of TFPB is (1694 cm⁻¹). -1 Significant attenuation was observed at 966 and 1610 cm⁻¹. -1 The presence of a strong stretching vibration peak of the ethylene bond (C=C) confirms the high degree of condensation polymerization of PVCOF-2.

[0060] The prepared PVCOF-2 was subjected to thermogravimetric analysis, and the thermogravimetric analysis results are shown in the figure below. Figure 7 As shown, thermogravimetric analysis revealed that the material structure remained relatively stable at 400℃ under nitrogen protection, indicating that the catalyst exhibits good stability at both room temperature and higher temperatures.

[0061] In addition, UV-Vis diffuse reflectance spectroscopy analysis was performed on PVCOF-2 (instrument model: Shimadzu UV-3600iPlus spectrophotometer), such as... Figure 8 As shown, the light absorption range of this material is around 690nm, exhibiting a strong visible light absorption capability.

[0062] Application Example 1

[0063] This application example illustrates the use of the vinylphenanthroline covalent organic framework material PVCOF-1 in a visible light photocatalytic hydrogen production system.

[0064] The photocatalytic hydrogen production activity of PVCOF-1 prepared in Example 1 was tested. 2 mg of the covalent organic framework catalyst PVCOF-1 was added to 100 mL of an aqueous solution containing 1.6 g of ascorbic acid in a beaker, resulting in a concentration of 20 mg / L. After ultrasonic dissolution, the solution was transferred to a reactor, and then 0.5 wt%, 1 wt%, 3 wt%, and 5 wt% of platinum precursor were added, respectively. The reactor was then connected to a Labsolar-6A system, and the entire system was evacuated for 20 min to completely remove air. Subsequently, the reactor was irradiated with a 300 W xenon lamp (CEL-HXF300H5, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) at a constant current of 20 A. A cutoff filter with λ ≥ 420 nm was used to allow visible light to pass through, and the reaction solution was irradiated from the top of the reactor for 1 h to carry out the photocatalytic reaction.

[0065] The amount of hydrogen generated was detected and analyzed by gas chromatography (GC-2014), and the visible light photocatalytic hydrogen evolution performance of PVCOF-1 as a catalyst under different platinum loading conditions was obtained as follows: Figure 9 As shown, from Figure 9 It can be seen that when the platinum loading is 0.5wt%, 1wt%, 3wt%, and 5wt%, the hydrogen evolution rate reaches 4746.05 μmol·h⁻¹. -1 ·g -1 5081.85 μmol·h -1 ·g -1 11525.3 μmol·h -1 ·g -1 and 10205.1 μmol·h -1 ·g -1 This indicates that catalyst PVCOF-1 has excellent hydrogen production performance.

[0066] Application Example 2

[0067] This application example illustrates the use of the vinylphenanthroline covalent organic framework material PVCOF-1 in a visible light catalytic oxygen generation system.

[0068] The photocatalytic oxygen evolution activity of PVCOF-1 prepared in Example 1 was tested. 2 mg of the covalent organic framework catalyst PVCOF-1 was added to 100 mL of an aqueous solution containing 1.6 g of ascorbic acid in a beaker, resulting in a concentration of 20 mg / L. After ultrasonic dissolution, the solution was transferred to a reactor, and then 0.5 wt%, 1 wt%, 3 wt%, and 5 wt% of cobalt precursor were added, respectively. The reactor was then connected to a Labsolar-6A system, and the entire system was evacuated for 20 min to completely remove air. Subsequently, the reactor was irradiated with a 300 W xenon lamp (CEL-HXF300H5, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) at a constant current of 20 A. A cutoff filter with λ ≥ 420 nm was used to allow visible light to pass through, and the reaction solution was irradiated from the top of the reactor for 1 h to carry out the photocatalytic reaction.

[0069] The amount of oxygen generated was detected and analyzed by gas chromatography (GC-2014), and the visible light photocatalytic oxygen evolution performance of PVCOF-1 as a catalyst under different cobalt loading conditions was obtained as follows: Figure 10 As shown, from Figure 10 It can be seen that when the cobalt loading is 0.5wt%, 1wt%, 3wt%, and 5wt%, the oxygen production reaches 1225.9 μmol·h⁻¹. -1 ·g -1 1522.6 μmol·h -1 ·g -1 2052.75 μmol·h-1 ·g -1 and 2061.95 μmol·h -1 ·g -1 This indicates that the catalyst PVCOF-1 has excellent oxygen production performance.

[0070] Application Example 3

[0071] This application example tests the photocatalytic hydrogen evolution performance of PVCOFs from Examples 1 and 2 under illumination for 6 hours with a platinum loading of 3 wt%.

[0072] The PVCOFs prepared in Examples 1 and 2 were subjected to photocatalytic hydrogen evolution activity tests. 2 mg of the covalent organic framework catalyst PVCOFs was added to 100 mL of an aqueous solution containing 1.6 g of ascorbic acid in a beaker, resulting in a concentration of 20 mg / L. After ultrasonic dissolution, the solution was transferred to a reactor, and 3 wt% of a platinum precursor was added. The reactor was then connected to a Labsolar-6A system, and the entire system was evacuated for 20 min to completely remove air. Subsequently, the reactor was irradiated with a 300 W xenon lamp (CEL-HXF300H5, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) at a constant current of 20 A. A cutoff filter with λ ≥ 420 nm was used to allow visible light to pass through, and the reaction solution was irradiated from the top of the reactor for 6 h to carry out the photocatalytic reaction.

[0073] The amount of hydrogen generated was detected and analyzed by gas chromatography (GC-2014), and the visible light photocatalytic hydrogen evolution performance of PVCOFs material with 3wt% platinum loading was as follows: Figure 11 As shown, from Figure 11 It can be seen that the hydrogen evolution amount reached 47115.5 μmol·h⁻¹. -1 ·g -1 and 19835.2 μmol·h -1 ·g -1 This indicates that PVCOFs have good stability in photocatalytic hydrogen production, and that PVCOF-1 has higher hydrogen production activity than PVCOF-2.

[0074] Application Example 4

[0075] This application example tests the photocatalytic oxygen evolution performance of PVCOFs from Examples 1 and 2 under illumination for 6 hours with a 3 wt% cobalt loading.

[0076] The PVCOFs prepared in Examples 1 and 2 were subjected to photocatalytic oxygen evolution activity tests. 2 mg of the covalent organic framework catalyst PVCOFs was added to 100 mL of an aqueous solution containing 1.6 g of ascorbic acid in a beaker, resulting in a concentration of 200 mg / L. After ultrasonic dissolution, the solution was transferred to a reactor, and 3 wt% of a cobalt precursor was added. The reactor was then connected to a Labsolar-6A system, and the entire system was evacuated for 20 min to completely remove air. Subsequently, the reactor was irradiated with a 300 W xenon lamp (CEL-HXF300H5, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) at a constant current of 20 A. A cutoff filter with λ ≥ 420 nm was used to allow visible light to pass through, and the reaction solution was irradiated from the top of the reactor for 6 h to carry out the photocatalytic reaction.

[0077] The amount of oxygen generated was detected and analyzed by gas chromatography (GC-2014), and the visible light photocatalytic oxygen evolution performance of PVCOFs material with a 3wt% cobalt loading was obtained as follows: Figure 12 As shown, from Figure 12 It can be seen that the oxygen evolution rate reached 5816.7 μmol·h⁻¹. -1 ·g -1 and 3209.65 μmol·h -1 ·g -1 This indicates that PVCOFs have good stability in photocatalytic oxygen production, and that PVCOF-1 has higher oxygen production activity than PVCOF-2.

[0078] Application Example 5

[0079] By comparing Application Examples 3 and 4, it is shown that the hydrogen evolution and oxygen evolution performance of the PVCOF-1 catalyst are significantly higher than those of the PVCOF-2 catalyst. This example tests the stability of the PVCOF-1 material in the visible light catalytic water splitting reaction.

[0080] The PVCOF-1 prepared in Example 1 was subjected to photocatalytic hydrogen evolution activity testing. 2 mg of the covalent organic framework catalyst PVCOFs was added to 100 mL of an aqueous solution containing 1.6 g of ascorbic acid in a beaker, resulting in a concentration of 200 mg / L. After ultrasonic dissolution, the solution was transferred to a reactor, and 3 wt% of a platinum precursor was added. The reactor was then connected to a Labsolar-6A system, and the entire system was evacuated for 20 min to completely remove air. Subsequently, the reactor was irradiated with a 300 W xenon lamp (CEL-HXF300H5, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) at a constant current of 20 A. A cutoff filter with λ ≥ 420 nm was used to allow visible light to pass through. The reaction solution was irradiated from the top of the reactor for 24 h to carry out the photocatalytic reaction.

[0081] The amount of hydrogen generated was detected and analyzed by gas chromatography (GC-2014). The 24-hour cycle performance of PVCOF-1 material for visible light photocatalytic water splitting and hydrogen evolution was as follows: Figure 13 As shown, this indicates that the catalytic activity of the catalyst remains stable.

[0082] The COFs materials of the two samples were subjected to impedance and photocurrent tests, respectively. The impedance and photocurrent test results are as follows: Figure 14 and Figure 15 As shown.

[0083] from Figure 14 It can be seen that the impedance arc radius of the PVCOF-1 sample is significantly smaller than that of the PVCOF-2 sample, indicating that the interfacial charge transport efficiency of the PVCOF-1 catalyst is higher, which is conducive to producing high photocatalytic performance.

[0084] In addition, from Figure 15 It can be seen that the photocurrent intensity of PVCOF-1 is significantly higher than that of PVCOF-2, indicating that the photogenerated charge separation and transfer of the PVCOF-1 catalyst are more favorable, thus resulting in higher photocatalytic efficiency.

[0085] As demonstrated in Application Examples 3 and 4, highly efficient hydrogen evolution and oxygen evolution can be achieved by combining triazine-based vinylphenanthroline covalent organic framework materials with sacrificial reagents and cocatalysts in specific ratios. This is due to the strong stability and electronic delocalization properties of carbon-carbon double bond COFs, and the fact that the nitrogen-rich triazine unit, as a building block, can adjust the electronic structure properties of COFs, thereby improving the photogenerated charge transfer efficiency of these materials and thus enhancing their catalytic performance.

[0086] The foregoing detailed examples of the present invention are merely preferred embodiments and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the present invention should still fall within the patent coverage of the present invention.

Claims

1. A method for preparing a vinylphenanthroline covalent organic framework material, characterized in that, The process includes the following steps: mixing reactant 2,9-dimethyl-1,10-phenanthroline and aldehyde monomer, adding solvent and catalyst, and preparing vinylphenanthroline covalent organic framework material by solvothermal reaction; wherein the aldehyde monomer is 1,3,5-tris(4-formylphenyl)triazine or 1,3,5-tris(p-formylphenyl)benzene.

2. The method for preparing a vinylphenanthroline covalent organic framework material according to claim 1, characterized in that, The molar ratio of the aldehyde monomer to 2,9-dimethyl-1,10-phenanthroline is 1:1.

5.

3. The method for preparing a vinylphenanthroline covalent organic framework material according to claim 1, characterized in that, The solvent is a mixed solution of N,N-dimethylformamide and o-dichlorobenzene, the catalyst is trifluoromethanesulfonic acid, and the volume ratio of N,N-dimethylformamide, o-dichlorobenzene and trifluoromethanesulfonic acid is 7:3:1.

5.

4. The method for preparing a vinylphenanthroline covalent organic framework material according to claim 1, characterized in that, The mass ratio of the reactant to the volume of the solvent and catalyst mixture is 12-13 mg / mL.

5. The method for preparing a vinylphenanthroline covalent organic framework material according to claim 1, characterized in that, The reaction temperature was 180 °C and the reaction time was 72-80 h. After the reaction, the product was washed sequentially with anhydrous methanol, tetrahydrofuran and dichloromethane, and then vacuum dried at 60-80 °C for 6-10 h.

6. The method for preparing a vinylphenanthroline covalent organic framework material according to claim 5, characterized in that, The washing process of the product is as follows: wash with anhydrous methanol 3-5 times, wash with dichloromethane 3-5 times, and wash with tetrahydrofuran 3-5 times.

7. A vinylphenanthroline covalent organic framework material obtained by the preparation method according to any one of claims 1-6.

8. The application of the vinylphenanthroline covalent organic framework material of claim 7 in photocatalytic water splitting for hydrogen and oxygen evolution.

9. The application according to claim 8, characterized in that, Vinylphenanthroline covalent organic framework material, sacrificial reagent and cocatalyst precursor are added to water, and water-decomposing reaction is carried out under visible light irradiation.

Citation Information

Patent Citations

  • Monatomic supported covalent organic framework material and preparation thereof, and application of monatomic supported covalent organic framework material in hydrogen production through water photolysis

    CN114570429A